Business Ethics – Deontologically Revisited - Micewski, Edwin R. (Journal of business ethics, 2007)
In this paper we look at business ethics from a deontological perspective. We address the theory of ethical decision-making and deontological ethics for business executives and explore the concept of “moral duty” as transcending mere gain and profit maximization. Two real-world cases that focus on accounting fraud as the ethical conception. Through these cases, we show that while accounting fraud – from a consequentialist perspective – may appear to provide a quick solution to a pressing problem, longer term effects of fraud and misconduct make ethical implications more apparent. Widely used compensation schemes also may have the tendency to fuel unethical behavior. We argue that an ethical reinvigoration of the business world can only be accomplished by encouraging the business realm to impose upon itself some measure of self-regulating along the lines of deontological ethics. Principles of deontology should guide executive decision-making particularly when executives are tempted to operate outside of codified legislation or are bound to act under judicial-free conditions.